The hidden perils of laser lead extractions: Managing internal mammary artery perforation - Wingtung M. Ma, BMed; Thomas M. Warburton, BMed, MTrauma; Alexandra Sim, MBBS, MD; Alasdair Watson, BMed (Hons), PhD, FRACS; Rajesh Subbiah, BSc (Med), MBBS, PhD, FRACP; David Evans, BSc, MBBS, FRACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Transvenous lead extraction for cardiac implantable electronic devices remains a high-risk procedure among profound evolutions of extraction techniques. Laser-assisted transvenous lead extraction is required with prolonged lead dwell times or failed mechanical extraction. Tertiary subspecialty support is crucial to mediate the small but significant risk of cardiovascular morbidity and mortality. We report a case of laser lead extraction complicated by internal mammary artery perforation and fistulization, salvaged with endovascular intervention. Multidisciplinary subspecialty support, skills, and infrastructure should be used for all these extractions.